IMPLEMENTASI METODE PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN USHUL FIQH KELAS XI AGAMA MA NIHAYATUL AMAL RAWAMERTA - Anisa Fitriah; Iwan Hermawan; Nur Aini Farida (STAI Pelabuhan Ratu, 2023)
Learning Ushul Fiqh in the eleventh grade at MA Nihayatul Amal faces serious challenges, where students often encounter difficulties in their studies. This phenomenon is reflected in the behavior of students who tend to merely pay attention to the teacher without actively participating, lack enthusiasm, and some even fall asleep in class. This research aims to explore the implementation, supporting factors, inhibiting factors, and the impact of applying the Problem Based Learning method to enhance learning outcomes in the Ushul Fiqh subject for the eleventh-grade Agama students at MA Nihayatul Amal Rawamerta. The research utilizes a participatory observation approach, in-depth interviews, and documentation to collect data. The results indicate that the implementation of the Problem Based Learning method involves several stages, namely planning, execution, and closure. During the planning stage, teachers design learning by detailing problems relevant to Ushul Fiqh content. In the execution stage, students actively engage in problem-solving, promoting active participation, and enhancing learning enthusiasm. The closure stage involves reflection on the conducted learning.